2019
DOI: 10.1111/nep.13240
|View full text |Cite
|
Sign up to set email alerts
|

Validation of acute kidney injury according to the modified KDIGO criteria in infants after cardiac surgery for congenital heart disease

Abstract: Application of the 3 criteria resulted in different AKI incidences, but each criterion could be useful for detecting risk factors for AKI. Notably, using m-KDIGO criteria provides more important subsequent postoperative outcomes. The m-KDIGO AKI criteria describe clinically relevant AKI in infants after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
3
30
0
2
Order By: Relevance
“…Patients with PPD placement also had statistically higher incidences of KDIGO Stage 1 and Stage 2 acute kidney injury in univariate analysis, with a rate of 24% that is consistent with prior literature [ 13 , 14 ]. Multivariable adjustment demonstrated no significant difference between the two groups for the incidence of KDIGO Stage 1 AKI, but the difference still trends toward significance for the incidence of KDIGO Stage 2.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with PPD placement also had statistically higher incidences of KDIGO Stage 1 and Stage 2 acute kidney injury in univariate analysis, with a rate of 24% that is consistent with prior literature [ 13 , 14 ]. Multivariable adjustment demonstrated no significant difference between the two groups for the incidence of KDIGO Stage 1 AKI, but the difference still trends toward significance for the incidence of KDIGO Stage 2.…”
Section: Discussionsupporting
confidence: 88%
“…Our age distribution also did not show a significant difference in the younger age group (i.e., nearly 54% of the patients younger than five years old). Of the affected cases, 87% belonged to RACHS-1 and RACHS-2, and almost half (45%) had cyanotic heart disease, whereas other reports had the majority of their patients in RACHS-2 and RACHS-3 [11,14]. The majority (66%) of AKI patients were diagnosed on their first postoperative day, and 64% of patients had their peak serum creatinine level within 24 hours after AKI diagnosis, which is similar to previous reports [14].…”
Section: Discussionsupporting
confidence: 86%
“…The frequency was lower than earlier reports, which may be due to our excluding the neonatal population in which the risk was highest. Ueno et al also used m-KIDGO criteria and found 37.5% AKI in the infant population [11]. Another study by Sethi et al used the AKIN criteria, as well as serum creatinine and baseline renal functions to define AKI based on the Schwartz formula [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Furthermore, the m-KDIGO AKI criteria describe clinically relevant AKI in infants after cardiac surgery. 5 The study subjects are patients aged <18 years who underwent cardiac under cardiopulmonary bypass with positive postoperative fluid balance. We are interested in knowing if the sCr levels used for diagnosis of AKI had been corrected based on the postoperative fluid balance.…”
Section: Sirmentioning
confidence: 99%